Wild Policy : Indigeneity and the Unruly Logics of Intervention. - Lea, Tess (Standford University Press, 2020)
Can there be good social policy? This book describes what happens to Indigenous policy when it targets the supposedly 'wild people' of regional and remote Australia. Tess Lea explores naturalized policy: policy unplugged, gone live, ramifying in everyday life, to show that it is policies that are wild, not the people being targeted. Lea turns the notion of unruliness on its head to reveal a policy-driven world dominated by short term political interests and their erratic, irrational effects, and by the less obvious protection of long-term interests in resource extraction and the liberal settler lifestyles this sustains. Wild Policy argues policies are not about undoing the big causes of enduring inequality, and do not ameliorate harms terribly well either—without yielding all hope.